Transboundary haze pollution and the legal framework at national level with respect to Malaysia and Singapore - Mat Seman, Nurulnabila Hanis; Mustafa, Maizatun; Rusli, Mohd Hazmi (Fakulti Undang-undang, Universiti Teknologi MARA, 2019)
This paper presents an overview of transboundary haze pollution whichhas been a serious environmental issue both in Malaysia and Singapore. This cross-border pollution that affects countries in the Southeast Asia region is the result of emission of smoke due to land or forest fires from Indonesia. Being geographically adjacent to Indonesia, both Malaysia and Singapore suffer more severe impacts as compared to other Southeast Asia countries. In the efforts to maintain good air quality and combating transboundary haze pollution, the aim of this paper are to analyse the concept of transboundary haze pollution and to examine causes of haze that originates from Indonesia. The paper then examines impacts of transboundary haze pollution to Malaysia and Singapore in the context of public health and economy. Finally the paper proceeds to discuss existing legal framework of both Malaysia and Singapore relevant to transboundary haze pollution control. The paper concludes that while the legal framework of both countries is sufficient in terms of controlling domestic haze pollution, such framework needs to be supported by international law in order for both countries to address the transboundary pollution and to protect their air quality more effectively.